THE ROLE OF THE DEPARTMENT «RUSSIAN AS A FOREIGN LANGUAGE» IN PROMOTION OF RUSSIAN LANGUAGE IN THE MODERN WORLD - Svetlana M. Petrova (Высшее образование в России, 2016)
The article discusses the role of the Federal University in the development of the educational policy in the Northeastern region of Russia. North-Eastern Federal University is one of the nine Federal universities of Russia, which calls to consolidate scientific and educational resources. It generates knowledge and innovation, creates conditions for technological break through in economy and sociocultural development of the North-Eastern Russian population. One of the main activities of the University is an international partnership. The article dwells on the university international projects including Double-Degree programs and enrolment of foreign students, and the role of the Department “Russian as a Foreign Language” in this process. The Department lecturers not only teach foreign citizens Russian language but also involve them in research work.